Diagnostic Accuracy of Focused Ultrasonography in Diagnosing Pneumoperitoneum, Taking CT Findings as Gold Standard - Ume Habiba, Bushra Maqsood, Nusrat Ullah Khan, Habib ur Rehman, Uzma Tasneem, Muhammad Amin (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Bedside assessment of patients with acute abdomen is extensively performed using emergency ultrasonography. Its purpose in the diagnosis of pneumoperitoneum, however, needs to be further validated. The study aimed to evaluate diagnostic accuracy of the focused ultrasonography in the diagnosis of pneumoperitoneum using the findings of the computed tomography (CT) as the gold standard. Materials and Methods: The present study is a cross-sectional study that was carried out in the Department of Radiology, Combined Military Hospital, Bahawalpur, between 22nd January 2019 and 21st July 2019. One hundred and sixty-nine patients who had acute abdomen and were aged between 15-55 years of both genders were involved. Patients who sustained penetrating abdominal injury, had chronic renal failure or were hypersensitive to the contrast agents were eliminated. The ultrasonography of the abdomen was carried out with a focused mode of image in the form of live two-dimensional (rapid B-mode) at a frequency of 36 MHz of the transducer. Then, an abdominal multislice CT was conducted prior to and after the administration of the intravenous contrast. A consultant radiologist interpreted the imaging findings and recorded the presence or the absence of pneumoperitoneum. The findings of the ultrasonography were contrasted with the CT findings. Results: The focused ultrasonography produced 77 true-positive, 79 true-negative, 4 false-positive, and 9 false-negative feasible results. The sensitivity, specificity, and positive and negative predictive values of 89.53, 95.18, 95.06 and 89.77 and overall diagnostic accuracy of 92.31 were achieved. Conclusions: Focused ultrasonography is a method that has a high diagnostic accuracy in the detection of pneumoperitoneal and a fast, portable, and non-invasive and cost-effective bedside imaging modality in patients who present with the acute abdomen. Keywords: Acute abdomen, focused abdominal sonography, pneumoperitoneum, sensitivity.